The total synthesis of 2',3'-dihydro-2'-hydroxyisopropyl-3'-furanocoumarin (VII) - Doğanca, Solmaz (Marmara Pharmaceutical Journal, 1985)
In this study the total synthesis of 2',3'-dihydro-2'-hydroxyisopropyl-3'-furanocoumarin (VII) was performed in seven steps.